Natural and nature based features for environmental enhancement and coastal storm risk management: a case study on Marco Island, Florida, United States - Dabees, Mohamed A.; Fleming, Matthew; Damon, Marc (Frontiers in Built Environment, 2022)
Natural and Nature-Based systems provide an opportunity for adaptive response to Coastal Storm Risk Management and Sea Level Rise. The Tigertail Lagoon/Sand Dollar Island Restoration on Marco Island, Florida, presents a case study designed to maintain and enhance an existing coastal barrier system consisting of a 3-km-long sand spit and tidal lagoon ecosystem that is otherwise evolving toward closure. The case study is part of a nature-based adaptive management plan to restore and stabilize the sandspit and tidal lagoon through cyclic use of sediment within the system. This approach seeks to preserve existing protective habitats and landforms that also serve as natural coastal barriers to protect upland development. Design of the restoration plan considers the functions of a wildlife nature preserve and evolution of complex tidal inlet morphologic features bordered by a heavily developed barrier Island. The design aims to restore and enhance a sandspit degraded by a sequence of storms since Major Hurricane Irma impacted Southwest Florida in 2017 and improve the existing deteriorated habitat by enhancing tidal exchange through restoration of the lagoon flow channel. Total wetland area will be increased by relocating the sand spit seaward of its present location to where it was located in approximately 2017. The reconstructed beach berm will provide enhanced resiliency to high frequency weather events. Sediment will be sourced from the existing sand spit and an innovative sand trap that will maintain the lagoon entrance open while providing beneficial re-use for excess sediment that continues to accumulate at the end of the spit. Components of the project were analyzed using existing engineering models and methods such as the Coastal Modeling System (CMS) and XBeach. Enhancing and preserving this barrier island feature and productive ecosystem provides an example of the enhanced coastal resiliency provided by natural and nature-based systems that are adaptable and responsive to sea level rise and ongoing coastal processes.